STUDI KASUS : ASUHAN KEBIDANAN PADA Ny.D MASA KEHAMILAN TRIMESTER III, PERSALINAN, NIFAS, NEONATUS DAN KELUARGA BERENCANA - Diana Sriyani; Septi Tri Aksari; Dahlia Arief Rantauni; Ellyzabeth Sukmawati (Pusat Riset dan Inovasi Nasional, 2022)
Midwives have an important role in strategies to reduce maternal mortality and infant mortality. Midwives are responsible for providing continuous and plenary services through health education, counseling, health promotion, and normal delivery assistance as well as early detection of referral cases by conducting comprehensive supervision, care and management of pregnant women, maternity, postpartum, BBL, neonates, and family planning. The author of this final project in the form of a case study using midwifery management approach using 7 steps varney and documented in the form of SOAP. The subjects of this case study were pregnant women in the third trimester, namely Mrs. D age 24 years gestational age 35+4 weeks followed by physiological pregnancy, maternity, puerperium, BBL, and family planning. The results of this case study obtained Ny. D diagnosis G2P0A1 gestational age 35+4 weeks with good circumstances, and physiological delivery. Physiological puerperium, physiological newborns, neonates upbringing and physiologically provided family planning. Comprehensive midwifery care in Ny. D found gaps in pregnancy that is less than 6x ANC examination, Tetanus Toxoid immunization is not complete. No gaps were found in the puerperium, BBL, and neonates. The conclusion from the results of this case study is that comprehensive midwifery care has been given to Mrs. D of pregnant, maternity, puerperal, BBL, neonate and family planning with the result that all care is carried out and the mother and baby are in good condition.